Micawber - Lithgow, John, 1945-; Payne, C. F. (New York : Simon & Schuster Books for Young Readers, 2002)
Micawber, a squirrel fascinated by art, leaves a museum with an art student and secretly uses her supplies to make his own paintings.
Keywords: Artists -- Fiction; Museums -- Fiction; Squirrels -- Fiction; Stories in rhyme